Enhancing next-generation ACP agribusiness through digitalisation - Ballantyne, Peter G.; Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2019)
Do innovative digital solutions improve the performance, competitiveness and profitability of farmer-oriented agribusinesses in African, Caribbean and Pacific (ACP) countries? Thirty practitioners attending a recent CTA workshop zoomed in on real cases to test this question, assessing what works, how and why and drawing out insights and lessons – actionable knowledge – for wider application. Workshop participants identified five intersecting drivers that explain why farmer-oriented agribusinesses invest in digitalisation: to reduce risk, raise productivity, increase efficiency, improve decisions, and enhance access to markets. Participants argued that digital interventions all serve one or more of these, depending on specific local needs and situations. A critical factor underpinning success or failure in these areas is the sustainability of the business models used to deliver value and services.